Advice for working moms (HBR working parents series., 2021)
"Working moms are pulled in all directions. Find the path that works for you. Your kid gets sick, so you leave work early-again. You're an expert at driving the carpool line and setting up for the morning meeting. You missed out on another stretch assignment because you don't have time. It's assumed you'll bake the treats for the fundraiser-and man the table. As a working mother you often draw the short straw. You carry most of the burden of caregiving and household chores-and your career suffers because of it. Bosses and coworkers assume that since you're focused on your family, you don't prioritize work, and they give crucial opportunities to those around you. Advice for Working Moms can help you alleviate this stress. Drawing on the wisdom of experts and parents alike, it will help you strike the right balance between family and work, all while navigating the long-standing bias against mothers and, more broadly, women in the workforce. You'll learn to: establish the boundaries you need at home and at work, negotiate flextime, time off, and maternity leave, facilitate your return to work after taking time off for caregiving, combat the "motherhood penalty", negotiate a more equal division of labor at home with your partner, say no to "office housework" and other menial tasks at work"--